Characterization and Anti-Inflammatory Activity of Ethanol Extract of Sikkam (Bischofia Javanica Blume) Stem Bark - Pangondian, Aswan; Nainggolan, Marline; Dalimunthe, Aminah (Asian Journal of Pharmaceutical Research and Development, 2020)
One of the medicinal plants that have been known since ancient times is sikkam (Bischofia javanica Blume) which is used as a natural dye in rattan and bamboo matting. Lawang Agung Village Community Kab. Lahat South Sumatra uses sikkam as a spice in cooking which is believed to be anti-inflammatory. This study aimed to assess the anti-inflammatory activity of ethanol extract of sikkam stem bark (Bischofia Javanica Blume) to reduce the edema volume of male white rats induced by carrageenan 1% and also to determine the effective dose of extract to reduce the volume of rat foot edema.Ethanol extract of sikkam bark (Bischofia Javanica Blume) was obtained by maceration. Anti-inflammatory activity test was divided into 5 groups. Group I (negative control) was given 0.5% CMC, Group II (positive control) was given diclofenac sodium 2.25 mg /kgBW, while Group III, IV and V were given ethanol extracts of sikkam bark with doses of 50,100 and 200 mg/kgBW respectively. Each rat was induced by 1% carrageenan subplantar injection. Examination of anti-inflammatory effects was measured using a digital plethysmometer at 30 to 360 minutes. Data were analyzed statistically using ANOVA (analysis of variance). The results showed that negative controls did not show an anti-inflammatory effect that had a significant difference with the other treatment groups. In conclusion, the ethanol extract of sikkam bark (Bischofia Javanica Blume) has effective anti-inflammatory activity at a dose of 200 mg/kgBW.